The digital handshake : seven proven strategies to grow your business using social media - Chaney, Paul, 1955- (Wiley & Sons, 2009)
Practical applications for using social media to boost your business. Even todayâ??s most successful businesses are seeing shrinking returns on their advertising and marketing dollars. The Digital Handshake explains why advertising and marketing are losing their effectiveness and how to solve the problem using social media to corral elusive consumers. It explains the best practical business applications in current use and how you can use them to ramp up your business. Using case studies gleaned from real businesses, author Paul Chaney shows you how companies both large and small that can tap s.